Associação entre resistência insulínica e osteoporose em pessoas vivendo com HIV assistidas por um serviço público de atenção secundária no interior do RS, Brasil - Caeran, Gabriela (2019)
The advent of antiretroviral therapy (HAART) considerably increased the life expectancy of people living with HIV (PVH). However, this increase in survival expose PVH to age-related morbidities, including chronic metabolic and bone diseases, which occur in a high and early way in this population. The time of infection of human immunodeficiency virus (HIV) and the type and duration of the ART affect the reduction of bone mineral density (BMD) and the onset of insulin resistance and it has been established that diabetes mellitus (DM) is associated with an increased risk of osteoporotic fractures. We aimed to study the prevalence of osteoporosis and insulin resistance, as well as the association between these factors in PVH and using TARV in the municipality of Santa Maria, Rio Grande do Sul. A cross-sectional study was conducted. It included people living with HIV over 50 years of age. Individuals registered for the receipt of antiretroviral drugs in the pharmacy of the university Hospital of Santa Maria/RS during the period 2016 to 2018 were invited to participate. Those who accepted to participate have responded a standardized questionnaire, performed a bone density scan and a spinal X-ray examination, underwent peripheral blood collection, and had their weight and height measured. Factors such as BMD, CD4 cell count, total cholesterol and fractions, glycemia and insulinemia were analyzed. Osteoporosis was defined according to the recommendations of the World Health Organization (1994 criteria) and insulin resistance was assessed by calculating HOMA-IR (values > 2.7 were considered positive). One hundred and one individuals agreed to participate in the study and 84 underwent both insulin and BMD measurements. The prevalence of osteoporosis was 19% in this sample. Vertebral fractures were twice as frequent in individuals with osteoporosis. Participants with osteoporosis had lower BMI and triglyceride values than those without it. The frequency of insulin resistance was 68.2%, and this diagnosis was associated with glucocorticoid use, smoking and BMI. It was not associated with viral load and CD4 count. HOMA-IR values were higher in the group without osteoporosis; however, this association disappeared after correction for BMI in the linear regression model. We conclude that PVH in our study that has insulin resistance has higher BMD. Therefore, further studies are needed to assess the effect of insulin resistance on fracture risk in PVH.